Factors Impeding Communication Skills Proficiency among Higher Learning Students: Study of College of Business Education and Dar es Salaam Institute of Technology - Makulilo, Prisca B.; Munishi, Emmanuel (GILE Journal of Skills Development, 2025)
Effective communication is essential for both academic and professional achievement in higher learning institutions. Although stakeholders in Tanzania have attempted several initiatives toward rectifying communication challenges, the difficulties students encounter in acquiring verbal and written competencies remain unresolved. This study investigates the main factors that impede the development of effective communication skills among students at two higher learning institutions. The study uses a qualitative design with in-depth interviews, focus group discussions, document reviews, and observations. Data were collected from 100 participants and analyzed using NVivo 12 software for thematic exploration. The findings identify four major barriers: teaching and learning methods; lecturer qualification; student-related behaviours; and poor English language proficiency. The findings offer practical insights for educators, curriculum planners, and policymakers aiming to enhance communication skills among Tanzanian students while contributing to the broader theoretical understanding of communication proficiency in multilingual, resource-constrained higher education contexts.